Analisis Pengaruh Pajak Daerah Dan Angkatan Kerja Terhadap Pertumbuhan Ekonomi Di Sumatera Utara Periode (2018-2021) - Aulia Nurfitriana; Ine Febrianti Siregar; Tinti Sriyani (Transformasi: Journal of Economics and Business Management, 2023)
GRDP is the total value of final goods and services produced by all economic units in a region. The GRDP level can describe the economic growth of a region. The high level of economic growth as indicated by the high GRDP value indicates that the region is experiencing progress in the economy. The purpose of this study is to see how much influence Taxes and the Labor Force have on GRDP in North Sumatra Province. The research method uses panel data analysis using data spanning 4 years starting from 2018 to 2021. Based on the research results, the results of Tax and Labor have a positive and significant effect on GRDP in North Sumatra.